Implantable Cardiac Defibrillator Lead Infective Endocarditis Due to Rothia Specie: A Rare Case in An Immunocompetent Man - Chukwuemeka A. Obi; Obiora Egbuche; Shirley I. Nwokike; Kenechukwu Mezue; Temidayo Abe; Kishen Bulsara; Titilope Olanipekun; Ifeoma Onuorah (Reviews in Cardiovascular Medicine, 2022)
Background: Rothia species are known to cause dental caries and periodontal disease, and infrequently cause native or prosthetic valve endocarditis mostly in immunocompromised persons. With an increasing use of implantable cardiac devices, early clinical suspicion and a rapid diagnosis of endocarditis is essential for optimal treatment to reduce complications and mortality. Bacteremic infection with Rothia dentocariosa in immunocompetent persons is uncommon. Pacemaker lead-related endocarditis caused by Rothia spp. is rare and management guidelines are not defined. Case Presentation: We report a rare case of implantable cardiac defibrillator (ICD) lead endocarditis in an immunocompetent patient that was caused by Rothia dentocariosa. Conclusions: Clinicians should be aware of this rare cause of CIED lead infections and should be acquainted with the optimal strategies of prompt antibiotic therapy and removal of the infected device/leads.